Hardening promoting material for hydraulic material, cement composition, and hardened body

By using hardening promoting materials containing calcium sulfaluminate, calcium organic acid salt, inorganic calcium compounds and inorganic sulfates in hydraulic materials, the problem of reduced fluidity of hydraulic materials during hardening is solved, and a more efficient hardening process and productivity improvement is achieved.

CN119768379APending Publication Date: 2025-04-04DENKA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380061130.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing hardening promoters lose fluidity immediately after mixing hydraulic materials with water, resulting in labor and time required to compact after pouring, which may lead to reduced productivity.

Method used

Hardening promoting materials for hydraulic materials containing calcium sulfaluminate, calcium organic acid salt, inorganic calcium compounds and inorganic sulfates other than calcium sulfate in a specified proportion are used. Through the combination of these components, hardening of hydraulic materials is promoted while maintaining their fluidity.

Benefits of technology

The fluid retention and initial strength presentation of hydraulic materials are achieved, reducing hardening time and improving productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005279657310000121
    Figure BDA0005279657310000121
  • Figure BDA0005279657310000131
    Figure BDA0005279657310000131
  • Figure BDA0005279657310000132
    Figure BDA0005279657310000132
Patent Text Reader

Abstract

A hardening promoting material for hydraulic materials, which contains 1-65% by mass of calcium sulfoaluminate, 0.5-75% by mass of an organic acid calcium salt, 1-55% by mass of an inorganic calcium compound, and 0.5-45% by mass of an inorganic sulfate other than calcium sulfate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hardening accelerating material for hydraulic materials, and a cement composition and a hardened body containing the same. Background Art

[0002] Hydraulic materials such as cement used in civil engineering and construction are generally hardened by mixing with water and leaving it to stand for a predetermined time. The hardening speed of hydraulic materials may also be affected by the ratio of the material to water, the surrounding ambient temperature, and the curing method. By using a mixed material that accelerates hardening, i.e., a hardening accelerating material, the time until the hydraulic material hardens can be shortened.

[0003] When the time until the hydraulic material hardens is shortened, the productivity of the work site is improved. For example, in the case of a hardened concrete used in a precast process for reinforced concrete buildings, etc., a cement composition is usually poured into a mold, left to stand for a predetermined time, and then cured by steam curing or the like to obtain a hardened concrete. However, by using a hardening accelerating material, the time until the initial strength that allows demolding can be shortened, so that the hardened concrete can be efficiently produced.

[0004] In addition, after pouring the cement composition, it is usually "compacted" using a vibrator or the like in order to evenly distribute the cement composition in the mold. However, if the fluidity of the cement composition immediately after pouring decreases, compaction requires labor and time, and productivity decreases.

[0005] Regarding the hardening accelerating material, for example, Patent Document 1 discloses a hardening accelerating material for a hydraulic material containing a predetermined amount of an inorganic sulfate, calcium sulfoaluminate, and an inorganic hydroxide. Patent Document 2 discloses a hardening accelerating material containing a Blaine specific surface area value of 4000 cm 2 / g or more of calcium sulfoaluminate and one or more selected from the group consisting of formates and lactates.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2014-19618

[0009] Patent Document 2: Japanese Patent Application Publication No. 2010-235399 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, since the hydraulic material using the above-mentioned hardening accelerating material loses fluidity immediately after being kneaded with water, compaction after pouring requires labor and time, and there is a concern that productivity will be reduced.

[0012] In view of the above, an object of the present invention is to provide a hardening accelerating material for a hydraulic material which can improve the fluidity retention and initial strength development of the hydraulic material.

[0013] Means for solving problems

[0014] The inventors of the present application have conducted intensive research to solve the above-mentioned problems, and as a result, have found that the problems can be solved by using a hardening accelerator for a hydraulic material containing calcium sulfoaluminate, an organic acid calcium salt, an inorganic calcium compound, and an inorganic sulfate other than calcium sulfate in a predetermined ratio, thereby completing the present invention. That is, the present invention is as follows.

[0015] [1] A hardening accelerator for a hydraulic material, comprising 1 to 65% by mass of calcium sulfoaluminate, 0.5 to 75% by mass of an organic acid calcium salt, 1 to 55% by mass of an inorganic calcium compound, and 0.5 to 45% by mass of an inorganic sulfate other than calcium sulfate.

[0016] [2] The hardening accelerator for a hydraulic material according to the above [1], wherein the inorganic calcium compound is one or more selected from the group consisting of calcium sulfate, calcium hydroxide, calcium carbonate and calcium oxide.

[0017] [3] The hardening accelerator for a hydraulic material according to [1] or [2], wherein the inorganic sulfate is one or more selected from the group consisting of sulfates, thiosulfates, sulfites, hydrogensulfites, pyrosulfates and pyrohydrogensulfites.

[0018] [4] A cement composition comprising cement and the hardening accelerator for a hydraulic material according to any one of [1] to [3] above.

[0019] [5] The cement composition according to [4] above, wherein the content of the hydraulic material hardening accelerator is 0.5 to 10% by mass.

[0020] [6] The cement composition according to [4] or [5] above, which is concrete containing aggregate.

[0021] [7] A hardened body obtained by hardening the cement composition described in [4] or [5] above.

[0022] [8] A hardened body obtained by hardening the cement composition described in [6] above.

[0023] [9] A method for producing a hardened body, wherein a cement composition comprising a hardening accelerator for a hydraulic material as described in any one of [1] to [3] above, cement and water is hardened by steam curing at a maximum temperature of 40 to 80°C for 2 to 8 hours.

[0024] Effects of the Invention

[0025] According to the present invention, it is possible to provide a hardening accelerating material for a hydraulic material which can improve the fluidity retention and initial strength development of the hydraulic material. DETAILED DESCRIPTION

[0026] Hereinafter, one embodiment of the present invention (this embodiment) will be described in detail, but the present invention is not limited to this embodiment. In the present invention, the so-called "hydraulic material" refers to a material that hardens when mixed with water, and the so-called "hardened body" refers to a substance hardened by cement paste, mortar, concrete, etc. It should be noted that, unless otherwise specified, the "%" and "parts" in this specification are based on mass.

[0027] [Hardening accelerator for hydraulic materials]

[0028] The hardening accelerating material for hydraulic material of the present invention contains 1 to 65% by mass of calcium sulfoaluminate, 0.5 to 75% by mass of organic acid calcium salt, 1 to 55% by mass of inorganic calcium compound and 0.5 to 45% by mass of inorganic sulfate other than calcium sulfate. The hardening accelerating material for hydraulic material not only accelerates the hardening of the hydraulic material when the hydraulic material is kneaded with water and hardened, but also hardens the hardening accelerating material for hydraulic material itself while accelerating the hardening.

[0029] (Calcium Sulphoaluminate)

[0030] Calcium sulfoaluminate in the present invention is a general term for hydraulic substances and water-containing salts represented by the chemical formula xCaO·yAl2O3·zCaSO4·mH2O (x, y, z are positive real numbers not equal to 0, and m is 0 or a positive real number). For example, in addition to blue calcite (3CaO·3Al2O3·CaSO4), AFt phase represented by ettringite (3CaO·Al2O3·3CaSO4·32H2O), AFm phase represented by monosulfate (3CaO·Al2O3·CaSO4·12H2O), and substances in which AFt phase and AFm phase coexist, etc. can also be cited. Calcium sulfoaluminate can be amorphous. In addition, a part of Al2O3 can be replaced by a trace amount of Fe2O3 or SiO2, etc., and a part of CaSO4 can be replaced by Ca(OH)2 or CaCO3, etc. It should be noted that in the present invention, since the fluidity of the hydraulic material may not be maintained and the strength during hardening may be reduced due to phase change, z in the above chemical formula xCaO·yAl2O3·zCaSO4·mH2O cannot be 0.

[0031] Calcium sulfoaluminate can be produced by using calcium oxide raw materials such as lime, sulfate raw materials such as gypsum, and aluminum oxide raw materials such as bauxite (aluminum hydroxide) as raw materials, mixing the raw materials in a predetermined ratio such as a molar ratio of CaO:CaSO4:Al2O3 of 3:3:1, etc., using a kiln, etc., calcining at about 1,500°C, and pulverizing. Alternatively, silicon dioxide or the like may be added to the material obtained by the primary calcination, heat-treating it, and pulverizing it.

[0032] The hardening accelerator for hydraulic material of the present invention contains 1 to 65 mass % of calcium sulfoaluminate, preferably 5 to 60 mass %, more preferably 10 to 55 mass %, and further preferably 20 to 45 mass %. If the content of calcium sulfoaluminate is outside the range of 1 to 65 mass %, the fluidity retention and initial strength development of the hydraulic material may not be good.

[0033] The Blaine specific surface area value of calcium sulfoaluminate (hereinafter, also referred to as "Blaine value") is preferably 1,000 to 6,000 cm 2 / g, more preferably 2,000 to 4,000 cm 2 / g, more preferably 2,200 to 3,800 cm 2 / g.

[0034] In addition, in the present invention, the Blaine specific surface area value is measured according to the specific surface area test described in JIS R 5201:2015 "Physical testing methods for cement".

[0035] (Organic acid calcium salt)

[0036] The hardening accelerator for hydraulic material of the present invention contains 0.5 to 75% by mass of organic acid calcium salt, preferably 1 to 70% by mass, more preferably 5 to 55% by mass, and further preferably 15 to 45% by mass. If the content of the organic acid calcium salt is less than 0.5% by mass, the fluidity retention and initial strength presentation of the hydraulic material may not be good, and if it exceeds 75% by mass, the initial strength presentation may not be good.

[0037] In the present embodiment, as the organic acid calcium salt, for example, calcium formate, calcium acetate, and calcium lactate can be used, and only one or more than two can be used. When two or more organic acid calcium salts are used, the total of the respective content ratios is taken as the content ratio of the organic acid calcium salt. In the present embodiment, from the viewpoint of initial strength presentation, calcium formate and / or calcium acetate are preferably used, and calcium formate is more preferably used.

[0038] (Inorganic calcium compounds)

[0039] The hardening accelerator for hydraulic material of the present invention contains 1 to 55% by mass of inorganic calcium compound, preferably 5 to 50% by mass, more preferably 15 to 40% by mass, and further preferably 18 to 30% by mass. If the content of the inorganic calcium compound is less than 1% by mass, the fluidity retention of the hydraulic material may not be good, and if it exceeds 55% by mass, the fluidity retention and initial strength presentation of the hydraulic material may not be good.

[0040] In the present embodiment, the inorganic calcium compound is preferably selected from more than one of the group consisting of calcium sulfate, calcium hydroxide, calcium carbonate and calcium oxide. When using more than two kinds of inorganic calcium compounds, the total of each containing ratio is used as the containing ratio of the inorganic calcium compound. In the present embodiment, from the viewpoint of initial strength presentation, calcium sulfate and / or calcium hydroxide are preferably used, more preferably calcium sulfate, and further preferably anhydrous calcium sulfate.

[0041] (Inorganic sulfate)

[0042] The hardening accelerator for hydraulic material of the present invention contains 0.5 to 45% by mass of inorganic sulfate other than calcium sulfate, preferably 1 to 40% by mass, more preferably 2.5 to 30% by mass, and further preferably 3 to 25% by mass. If the content ratio of the inorganic sulfate other than calcium sulfate is outside the range of 0.5 to 45% by mass, the fluidity retention and initial strength development of the hydraulic material may not be good.

[0043] In the present embodiment, the inorganic sulfate is preferably selected from one or more of the group consisting of sulfate, thiosulfate, sulfite, bisulfite, pyrosulfate and pyrosulfite. When two or more inorganic sulfates are used, the total of their respective content ratios is used as the content ratio of the inorganic sulfate. As inorganic substances forming salts, alkali metals and alkaline earth metals are preferred. In the present embodiment, from the viewpoint of initial strength presentation, sulfate and / or thiosulfate are preferably used, more preferably sodium sulfate, aluminum sulfate, sodium thiosulfate and potassium aluminum sulfate, further preferably sodium sulfate and aluminum sulfate, wherein, from the viewpoint of maintaining good fluidity, sodium sulfate is further preferred. When sodium sulfate is used, an anhydrous substance is more preferred.

[0044] [Cement composition]

[0045] The cement composition according to the present embodiment contains a hardening accelerator for a hydraulic material and cement.

[0046] As cement, there is no particular limitation, and various Portland cements such as ordinary, early strength, super early strength, low heat and medium heat can be enumerated, various mixed cements formed by mixing blast furnace slag, fly ash, silica fume etc. in these Portland cements, environmentally harmonious cement (environmentally friendly cement) manufactured with urban garbage incineration ash and sewage sludge incineration ash as raw materials, commercially available micro-cement, white cement etc., and various cements can also be used after being micro-powdered. In addition, the cement adjusted by increasing and decreasing the amount of the components (such as gypsum etc.) used in common cement can also be used. In addition, cements formed by combining two or more of them can also be used. From the viewpoint of improving the initial strength presentation, it is preferred to select ordinary Portland cement and early strength Portland cement, even if blast furnace cement and fly ash cement with low initial strength presentation are used, early demoulding can be achieved.

[0047] That is, from the viewpoint of production cost and strength development, the Blaine value of the cement used in the present invention is preferably 2,500 to 7,000 cm 2 / g, more preferably 2,750 to 6,000 cm 2 / g, more preferably 3,000 to 4,500 cm 2 / g.

[0048] The content of the hardening accelerator for hydraulic material in the cement composition is preferably 0.5 to 10% by mass, more preferably 1.0 to 9.0% by mass, and further preferably 2.5 to 8.0% by mass. If the content of the hardening accelerator for hydraulic material in the cement composition is within the above range, the fluidity retention and initial strength development of the hydraulic material can be improved.

[0049] The flow value of the cement composition before pouring is preferably 160 to 230, more preferably 170 to 220, and further preferably 190 to 200. If the flow value of the cement composition is within the above range, pouring and compaction are easy, and workability is improved. In addition, the change rate of the flow value (flow change rate) of the cement composition after kneading for 1 hour is preferably less than 20%, more preferably less than 15%, and further preferably less than 10%. If the flow change rate of the cement composition is within the above range, even if pouring is performed 1 hour after the cement composition is kneaded, pouring and compaction are easy, and workability is improved.

[0050] In the present invention, the flow value can be measured according to the method specified in JIS R 5201: 2015 "Physical testing methods for cement". The flow change rate can be obtained by subtracting the value calculated by (flow value after 1 hour of kneading) / (flow value immediately after kneading) × 100 (%) from 100%.

[0051] The cement composition preferably comprises aggregate. That is, the cement composition is preferably a concrete comprising aggregate (fine aggregate and coarse aggregate). As the aggregate used, the fine aggregate and coarse aggregate similar to those used in common cement mortar and concrete can be used. That is, river sand, river gravel, mountain sand, mountain gravel, crushed stone, crushed sand, limestone aggregate, lime sand, silica sand, colored sand, artificial aggregate, blast furnace slag aggregate, sea sand, sea gravel, artificial light aggregate and heavy aggregate etc. can be used, and they can also be combined.

[0052] The content of the aggregate is preferably 40 to 250 parts by mass, more preferably 50 to 230 parts by mass, and even more preferably 60 to 200 parts by mass relative to 100 parts by mass of cement in the cement composition. By making the content of the aggregate within the above range, the fluidity retention and initial strength presentation of the hydraulic material can be improved.

[0053] The cement composition may contain an alkali metal carbonate. By making the cement composition contain an alkali metal carbonate, it is easy to make the fluidity retention and initial strength development good. As the alkali metal carbonate, sodium carbonate, potassium carbonate, lithium carbonate, sodium bicarbonate, potassium bicarbonate and lithium bicarbonate can be mentioned, and they can also be combined.

[0054] The content of the alkali metal carbonate is preferably 1 to 6 parts by mass, more preferably 2 to 5 parts by mass, relative to 100 parts by mass of cement in the cement composition in terms of solid content. By making the content of the alkali metal carbonate within the above range, it is easy to make the fluidity retention and initial strength development good.

[0055] The cement composition may contain silica fine powder. By making the cement composition contain silica fine powder, it is easy to make the fluidity retention and initial strength presentation good. Examples of silica fine powder include latent hydraulic materials such as water-quenched blast furnace slag fine powder, fly ash, volcanic ash materials such as silica fume, among which silica fume is preferred. The type of silica fume is not limited. From the viewpoint of fluidity, it is more preferred to use silica fume containing less than 10% ZrO2 as an impurity and acidic silica fume. The so-called acidic silica fume refers to an acidic substance showing that the pH of the supernatant when 1g of silica fume is added to 100mL of pure water and stirred is less than 5.0.

[0056] The fineness of the silica powder is not particularly limited. Generally, the Blaine value of water-quenched blast furnace slag powder and fly ash is 3,000 to 9,000 cm 2 / g, and the BET specific surface area of ​​silica fume is between 20,000 and 300,000 cm 2 / g range.

[0057] The content of the silica fine powder is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and further preferably 3 to 12 parts by mass relative to 100 parts by mass of cement in the cement composition. By making the content of the silica fine powder above the above lower limit, it is easy to make the fluidity retention and initial strength presentation good. In addition, by making the content of the silica fine powder below the above upper limit, it is easy to make the fluidity retention better.

[0058] The cement composition may contain a defoamer within a range that does not adversely affect the performance. The defoamer is used to suppress the amount of air entrained during mixing. The type of defoamer is not particularly limited as long as it does not significantly adversely affect the strength characteristics of the hardened mortar, and both liquid and powdered forms can be used. For example, polyether defoamers, esters of polyols, polyol defoamers such as alkyl ethers, alkyl phosphate defoamers, silicone defoamers, etc. can be cited.

[0059] The content of the defoamer is preferably 0.002 to 0.5 parts by mass, more preferably 0.005 to 0.45 parts by mass, and further preferably 0.01 to 0.4 parts by mass relative to 100 parts by mass of cement in the cement composition. By making the content of the defoamer above the lower limit, the defoaming effect can be fully exhibited, and by making the content of the defoamer below the upper limit, it is easy to make the fluidity retention good.

[0060] In addition, the cement composition may use one or more of the following substances within the range that does not adversely affect the performance and within the range that does not substantially impair the purpose of the present invention: gas foaming material, water reducing agent, AE agent, rust inhibitor, hydrophobic agent, antibacterial agent, colorant, antifreeze agent, limestone fine powder, slow-cooled blast furnace slag fine powder, sewage sludge incineration ash or its molten slag, municipal waste incineration ash or its molten slag, and pulp sludge incineration ash and other mixed materials, thickeners, shrinkage reducing agents, polymers, clay minerals such as bentonite and sepiolite, and anion exchangers such as hydrotalcite.

[0061] [Hardened body]

[0062] The hardened body involved in the present embodiment is formed by hardening the cement composition. The hardened body is usually hardened by kneading the cement composition with water so that the cement as a hydraulic material undergoes a hydration reaction. The amount of water for kneading the hardened body is not particularly limited, and is preferably 10 to 70 parts by mass, more preferably 14 to 65 parts by mass, and further preferably 16 to 60 parts by mass relative to 100 parts by mass of the cement composition. If the amount of water for kneading is within the above range, it is easy to make the initial strength of the hydraulic material present good.

[0063] The hardened body is obtained by mixing the cement composition with water and then letting it stand to harden. It can be obtained more effectively by filling (pouring) into a mold frame after mixing and curing; or directly pouring, spraying or applying it to the construction site after mixing.

[0064] The compressive strength of the hardened body depends on the type of cement used. It is preferably 10.5 to 15.0 N / mm2 6 hours after pouring. 2 , more preferably 11.0 to 14.0 N / mm 2 , more preferably 12.0 to 13.0 N / mm 2 In addition, when the material is 7 days old, it is preferably 40.0 to 50.0 N / mm 2 , more preferably 41.0 to 48.0 N / mm 2 , more preferably 42.0 to 46.0 N / mm 2 .

[0065] In addition, in the present invention, the compressive strength can be measured according to the method specified in JIS R 5201:2015 "Physical testing methods for cement".

[0066] [Method for producing hardened body]

[0067] The method for manufacturing a hardened body according to the present embodiment is a method for filling (pouring) a cement composition containing a hardening accelerating material for hydraulic material, cement and water into a mold frame to harden it. The method for manufacturing a hardened body preferably includes a kneading step of kneading a hardening accelerating material for hydraulic material, cement and water, a pouring step of filling the kneaded cement composition into a mold frame, and a curing step of curing the cement composition filled into the mold frame.

[0068] The mixing method in the mixing step is not particularly limited, and the materials may be mixed during construction, or a part or all of the materials may be mixed in advance. As a mixing device, any existing device may be used, such as a tilting mixer, an Omni mixer, a Henschel mixer, a V-type mixer, a Pro-shear mixer, and a Nauta mixer.

[0069] The pouring method in the pouring step can be performed by a known method. The temperature of the cement composition during pouring is preferably 0 to 50° C., more preferably 10 to 40° C. When the temperature of the cement composition during pouring is within the above range, the hardened body can be easily demolded at an early stage.

[0070] The manufacturing method of the hardened body preferably further comprises a compacting process after the pouring process. The compacting method can use a known method, and preferably uses a vibrator from the viewpoint of workability. With regard to the cement composition containing the hydraulic material hardening accelerating material of the present invention, since fluidity is well maintained before pouring, compacting can be easily performed, and the cement composition can be evenly distributed in the mold frame, and in addition, bubbles mixed in during pouring can be removed.

[0071] As a curing method used in the curing process, steam curing using a curing chamber, a heating plate, etc. is preferably used from the viewpoint of improving productivity. For steam curing, generally, the temperature of the atmosphere around the object is raised, and the curing is performed while maintaining a constant temperature while maintaining an appropriate humidity. As conditions for steam curing, a maximum temperature of 40 to 80°C and a curing time of 2 to 8 hours are preferred, a maximum temperature of 40 to 75°C and a curing time of 2.5 to 7.5 hours are more preferred, and a maximum temperature of 45 to 60°C and a curing time of 3 to 7 hours are further preferred. If the steam curing is performed while the maximum temperature of the atmosphere around the cement composition during steam curing is within the above range and the curing time is within the above range, early demolding of the hardened body can be easily achieved.

[0072] The relative humidity around the cement composition during steam curing is preferably 50% RH or more, more preferably 75% RH or more, and further preferably 90% RH or more. The upper limit is not limited and can be 100% RH. If the relative humidity around the cement composition during steam curing is within the above range, early demoulding of the hardened body is easily achieved.

[0073] The curing process preferably includes a pre-curing process. As the pre-curing condition, it is preferred to maintain the temperature at a constant temperature within the range of 10 to 50° C. for about 1 to 3 hours. By including the pre-curing process in the curing process, the temperature inside the poured cement composition can be made uniform, and temperature cracks caused by the temperature difference between the inside and the outside can be easily prevented.

[0074] The curing step preferably includes a heating step. As a heating method, a known method can be used, preferably heating at a heating rate of 10 to 30°C / hour, more preferably heating at a heating rate of 12 to 28°C / hour, and further preferably heating at a heating rate of 15 to 25°C / hour. If the heating rate in the heating step is within the above range, temperature cracks caused by a rapid temperature rise in the cement composition can be prevented, and hardening can be further promoted.

[0075] The curing step preferably includes a heat preservation step. As a heat preservation method, a known method can be used, preferably maintaining a constant temperature in the range of 40 to 80° C. for 1 to 8 hours, more preferably maintaining a constant temperature in the range of 40 to 75° C. for 1 to 6 hours, and further preferably maintaining a constant temperature in the range of 45 to 65° C. for 2.5 to 5 hours. In the heat preservation step, by maintaining a constant temperature in the above range, the poured cement composition can be uniformly hardened, and early demolding can be easily achieved.

[0076] The method for manufacturing a hardened body preferably includes a natural cooling step after the curing step. In the natural cooling step, the hardened body obtained by the curing step is naturally cooled in a room temperature atmosphere. The cooling time is not particularly limited, as long as it can be cooled to a temperature at which the hardened body can be easily demolded, and can be about 0.5 to 2 hours. By including a natural cooling step after the curing step, temperature cracks of the hardened body can be prevented.

[0077] Example

[0078] Hereinafter, the present invention will be further described based on experimental examples, but the present invention is not limited to these.

[0079] <Experimental Example 1>

[0080] Using the following materials, a mortar having a water / cement ratio of 45% and a cement to aggregate ratio of 1:2.5 (mass ratio) was prepared. A water reducing agent was added to the obtained mortar in the ratio described in Table 1, and the hydraulic material and the hardening accelerating material of the composition shown in Table 1 were mixed in such a manner that the mixing amount became the ratio shown in Table 1, thereby preparing a cement composition. The flow value of the obtained cement composition was measured, and the flow change rate was calculated. They are all described in Table 1.

[0081] In addition, the prepared cement composition was filled into a mold frame of size 4×4×16 cm, and then steam cured to obtain a hardened body. The steam curing conditions were as follows: pre-curing at 20°C for 1 hour, heating at a rate of 20°C / hour for 1.5 hours, keeping at 50°C for 3 hours, and naturally cooling for 0.5 hours. The compressive strength of the hardened body obtained was measured. The results are recorded in Table 1.

[0082] It should be noted that the calcium sulfoaluminate used was prepared by mixing primary reagent calcium carbonate, calcium sulfate dihydrate and aluminum hydroxide at a molar ratio of CaO:CaSO4:Al2O3 of 4:3:1, calcining at 1,400°C for 2 hours, allowing to cool to room temperature, and pulverizing until the Blaine value reached 3,500 cm 2 / g.

[0083] (Materials used)

[0084] Cement: Ordinary Portland cement (commercial product), Blaine value 3,200 cm 2 / g, specific gravity 3.15g / cm 3 .

[0085] Water: tap water.

[0086] Aggregate: Fine aggregate, river sand produced in the Himekawa River system in Niigata Prefecture.

[0087] Water reducing agent: polycarboxylic acid-based high-performance water reducing agent (commercially available product).

[0088] Calcium sulphoaluminate: Trial product, Blaine value 3,500cm 2 / g.

[0089] Calcium formate (organic acid calcium salt): reagent.

[0090] Calcium sulfate (inorganic calcium compound): reagent.

[0091] Sodium sulfate (inorganic sulfate): anhydrous, reagent.

[0092] (Measurement Items)

[0093] Flow rate change: According to the method specified in JIS R 5201:2015 "Physical testing methods for cement", the flow values ​​of the cement composition immediately after mixing and 1 hour after mixing were measured. The flow values ​​immediately after mixing were all about 200. Using the measured flow values, the flow rate change was calculated as (flow rate change) = 1-(flow value 1 hour after mixing) / (immediately after mixing) × 100.

[0094] Compressive strength: The compressive strength of the hardened material was measured 6 hours after steam curing (immediately after demolding) and 7 days after steam curing according to the method specified in JIS R 5201:2015 "Physical testing methods for cement".

[0095] [Table 1]

[0096] Table 1

[0097]

[0098] The results shown in Table 1 confirmed that the fluidity retention and initial strength development of the cement composition can be improved by using a hydraulic hardening accelerator containing calcium sulfoaluminate, an organic acid calcium salt, an inorganic calcium compound, and an inorganic sulfate other than calcium sulfate in a predetermined ratio.

[0099] <Experimental Example 2>

[0100] Mortar, cement composition and hardened product were prepared in the same manner as in Experimental Example 1, and the flow rate change and compressive strength were measured. The results are also shown in Table 2.

[0101] (Organic acid calcium salt)

[0102] Calcium acetate: Reagent.

[0103] Calcium lactate: Reagent.

[0104] [Table 2]

[0105] Table 2

[0106]

[0107] The results shown in Table 2 confirmed that the fluidity retention and initial strength development of the cement composition can be improved by using calcium formate, calcium acetate and calcium lactate as the organic acid calcium salt contained in the hardening accelerator for hydraulic material. Among them, it was confirmed that the initial strength development of the hardened body can be improved particularly when calcium formate is contained.

[0108] <Experimental Example 3>

[0109] As the inorganic calcium compound contained in the hardening accelerating material for hydraulic material, in addition to calcium sulfate, calcium hydroxide, calcium carbonate and calcium oxide were used in the proportions shown in Table 3. The same operation as in Experimental Example 1 was carried out to prepare mortar, cement composition and hardened body, and the flow change rate and compressive strength were measured. The results are also recorded in Table 3.

[0110] [Table 3]

[0111] Table 3

[0112]

[0113] The results shown in Table 3 confirmed that the cement composition can have good fluidity retention and initial strength development by using calcium sulfate, calcium hydroxide, calcium carbonate and calcium oxide as the inorganic calcium compound contained in the hardening accelerating material for hydraulic material. Among them, it was confirmed that the cement composition can have good fluidity retention in particular when calcium sulfate is contained.

[0114] (Inorganic calcium compounds)

[0115] Calcium Hydroxide: Reagent.

[0116] Calcium carbonate: Reagent.

[0117] Calcium oxide: Reagent.

[0118] <Experimental Example 4>

[0119] Mortar, cement composition and hardened product were prepared in the same manner as in Experimental Example 1, and the flow rate change and compressive strength were measured, except that, in addition to sodium sulfate, aluminum sulfate, potassium aluminum sulfate and sodium thiosulfate were used in the proportions shown in Table 4 as the inorganic sulfate contained in the hardening accelerating material for hydraulic material. The results are also shown in Table 4.

[0120] (Inorganic sulfate)

[0121] Aluminum sulfate: Reagent.

[0122] Potassium aluminum sulfate: reagent.

[0123] Sodium Thiosulfate: Reagent.

[0124] [Table 4]

[0125] Table 4

[0126]

[0127] From the results shown in Table 4, it was confirmed that the fluidity retention and initial strength development of the cement composition can be improved by using sodium sulfate, aluminum sulfate, potassium aluminum sulfate and sodium thiosulfate as the inorganic sulfate contained in the hardening accelerator for hydraulic material. Among them, it was confirmed that the initial strength development can be further improved when sodium sulfate and aluminum sulfate are contained, and in particular, the fluidity retention can be further improved when sodium sulfate is contained.

[0128] <Experimental Example 5>

[0129] Mortar, cement composition and hardened product were prepared in the same manner as in Experimental Example 1 except that the mixing amount of the hardening accelerator for hydraulic material was set to the ratio shown in Table 5, and the flow change rate and compressive strength were measured. The results are also shown in Table 5.

[0130] [Table 5]

[0131] Table 5

[0132]

[0133] From the results shown in Table 5, it was confirmed that the fluidity retention and initial strength development of the cement composition can be improved by adjusting the mixing amount of the hardening accelerating material for a hydraulic material to be within a predetermined range.

[0134] <Experimental Example 6>

[0135] Mortar, cement composition and hardened body were prepared in the same manner as in Experimental Example 1 except that blast furnace cement and fly ash cement were used as cement in the cement composition, and the flow rate change and compressive strength were measured. The results are collectively shown in Table 6.

[0136] (cement)

[0137] Blast furnace type B cement: commercially available, Blaine value 3,200cm 2 / g, specific gravity 3.15g / cm 3 .

[0138] Blast furnace C cement: Commercially available, Blaine value 3,500cm 2 / g, specific gravity 3.15g / cm 3 .

[0139] Fly ash cement type B: commercially available, Blaine value 3,200cm 2 / g, specific gravity 3.15g / cm 3 .

[0140] [Table 6]

[0141] Table 6

[0142]

[0143] From the results shown in Table 6, it was confirmed that even when blast furnace cement or fly ash cement was used as cement for the cement composition, the fluidity retention and initial strength development of the cement composition could be improved.

[0144] <Experimental Example 7>

[0145] In addition to the hardening accelerator for hydraulic material of the same composition as No. 1-2 in Table 1 and the fine aggregate used in Experimental Example 1, coarse aggregate (river gravel produced in the Himekawa River system in Niigata Prefecture) was added as aggregate, and blast furnace slag fine powder (commercially available) was used to mix and knead the mixture so as to have the composition shown in Table 7 to prepare cement compositions (concrete), and the slump change was measured. The prepared cement compositions were hardened under the following conditions 1 or 2 to prepare The compressive strength of the hardened concrete was measured. The results are recorded in Table 7.

[0146] (Measurement Items)

[0147] Slump change: According to the method specified in JIS R 1101:2020 "Slump test method for concrete", the slump values ​​of concrete immediately after mixing and 1 hour after mixing are measured. The slump value immediately after mixing is about 12.0 cm. Using the measured slump values, the slump change is calculated as (slump change) = (slump value immediately after mixing) / (slump value 1 hour after mixing).

[0148] Compressive strength: Measured according to the method specified in JIS A 1108:2018 "Test method for compressive strength of concrete".

[0149] (Condition 1)

[0150] Concrete was produced by steam curing. The steam curing conditions were: pre-curing at 20°C for 1 hour, heating at a rate of 20°C / hour for 1.5 hours, keeping at 50°C for 3 hours, and natural cooling for 0.5 hours.

[0151] (Condition 2)

[0152] Make concrete at 30℃ and keep it for 12 hours.

[0153] [Table 7]

[0154] Table 7

[0155]

[0156] *W / C = water / cement, W / B = water / binding material

[0157] From the results shown in Table 7, it was confirmed that even when the cement composition contained coarse aggregate and blast furnace slag fine powder, fluidity retention and initial strength development properties could be improved.

[0158] The above results confirmed that the cement composition can have good fluidity retention and initial strength development properties by containing calcium sulfoaluminate, organic acid calcium salt, inorganic calcium compound and inorganic sulfate in the hardening accelerating material for a hydraulic material of the present invention at a predetermined ratio.

[0159] Industrial Applicability

[0160] By making the hardening accelerating material for hydraulic material of the present invention contain calcium sulfoaluminate, organic acid calcium salt, inorganic calcium compound and inorganic sulfate other than calcium sulfate in a predetermined ratio, the fluidity retention and initial strength development of the hydraulic material can be improved. Therefore, it can be widely used in civil engineering and construction fields such as concrete hardening bodies used in precast processes.

Claims

1. A hardening accelerator for a hydraulic material, comprising 1 to 65% by mass of calcium sulfoaluminate, 0.5 to 75% by mass of an organic acid calcium salt, 1 to 55% by mass of an inorganic calcium compound, and 0.5 to 45% by mass of an inorganic sulfate other than calcium sulfate.

2. The hardening accelerating material for a hydraulic material according to claim 1, wherein The inorganic calcium compound is one or more selected from the group consisting of calcium sulfate, calcium hydroxide, calcium carbonate, and calcium oxide.

3. The hardening accelerating material for a hydraulic material according to claim 1 or 2, wherein: The inorganic sulfate is at least one selected from the group consisting of sulfates, thiosulfates, sulfites, bisulfites, pyrosulfates, and pyrobisulfites.

4. A cement composition comprising cement and the hardening accelerating material for a hydraulic material according to claim 1 or 2.

5. The cement composition according to claim 4, wherein The content of the hardening accelerating material for the hydraulic material is 0.5 to 10% by mass.

6. The cement composition according to claim 4, which is concrete comprising aggregates.

7. A hardened body obtained by hardening the cement composition according to claim 4.

8. A hardened body obtained by hardening the cement composition according to claim 6.

9. A method for producing a hardened body, wherein: The cement composition comprising the hardening accelerating material for a hydraulic material according to claim 1, cement and water is hardened by steam curing at a maximum temperature of 40 to 80°C for 2 to 8 hours.

Citation Information

Patent Citations

  • Cement admixture and cement composition

    JP2010235399A

  • Curing accelerator for hydraulic material, hydraulic composition, method for manufacturing hydraulically cured object, and hydraulically cured object

    JP2014019618A